White Quantum‐Dot LEDs: Efficient and Color Stable White Quantum‐Dot Light‐Emitting Diodes with External Quantum Efficiency Over 23% (Advanced Optical Materials 16/2018). Issue 16 (20th August 2018) - Zhang, Heng; Su, Qiang; Sun, Yizhe; Chen, Shuming
Abstract : Highly efficient and color stable white quantum dot light‐emitting diodes have been demonstrated by Shuming Chen and co‐workers (article number1800354 ) by using a red/green/blue three‐unit tandem or a blue/green:red two‐unit tandem structure. The demonstrated tandem devices exhibit a pure white emission and an impressively high external quantum efficiency of 23%.